Fracture behavior and deformation mechanisms in nanolaminated crystalline/amorphous micro-cantilevers. (November 2019) - Wang, Y.Q.; Fritz, R.; Kiener, D.; Zhang, J.Y.; Liu, G.; Kolednik, O.; Pippan, R.; Sun, J.
Abstract: In order to quantify the fracture toughness and reveal the failure mechanism of crystalline/amorphous nanolaminates (C/ANLs), in-situ micro-cantilever bending tests were performed on Ag/Cu–Zr and Mo/Cu–Zr C/ANLs in a scanning electron microscope over a wide range of cantilever widths from several microns to the submicron scale. The results demonstrate that the fracture behavior was strongly influenced by sample size and constituent phases, respectively. The Ag/Cu–Zr micro-cantilevers failed in a ductile manner, with fracture toughnesses higher than the Mo/Cu–Zr samples that exhibited brittle failure. Both materials also displayed different cantilever width-dependences of fracture toughness. The Ag/Cu–Zr beams showed a fracture toughness that increases with the cantilever width, mainly due to a size-dependent constraining effect on the deformation of the crystalline phase. For the Mo/Cu–Zr beams, the fracture toughness decreased gradually to a low plateau as the cantilever width exceeded ∼1500 nm, which can be rationalized by a transition in stress condition. The underlying fracture mechanism of the Ag/Cu–Zr micro-cantilevers was identified as the interconnection of microcracks initiated in the amorphous Cu–Zr layers, compared to a catastrophically penetrating crack propagation in the Mo/Cu–Zr samples. The discrepancy in size-dependent fracture behavior between the two material systems is discussed in terms of plastic energy dissipation of ductile phases, crack tip blunting, crack bridging and the effect of strain gradient in the plastic zone on crack propagation. Graphical abstract: Image 1